2021
DOI: 10.7759/cureus.19457
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Usefulness of YouTube Videos on Retinal Detachment Surgery

Abstract: Introduction The aim of this study is to evaluate the usefulness of YouTube videos about retinal detachment surgery as a resource. Methods The first 100 videos were evaluated when they were scanned by typing "retinal detachment surgery " in the YouTube search engine. These videos were also analyzed and scored using DISCERN, Journal of the American Medical Association (JAMA), and Global Quality (GQ) scoring systems. Results The DISCERN score of the evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The reliability and quality of YouTube videos on eye diseases and their treatments have been investigated in many studies. [11][12][13][14][15][16][17][18][19] Sakalliog ˘lu and Garip 11 have reported in their study on YouTube videos on dry eye that only a small portion of the videos were of good quality, and that the videos of medical institutes and academic centers were of higher quality than the videos of physicians. Bae and Baxter 12 have evaluated YouTube videos on cataract surgery and found them inadequate in terms of patient training.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability and quality of YouTube videos on eye diseases and their treatments have been investigated in many studies. [11][12][13][14][15][16][17][18][19] Sakalliog ˘lu and Garip 11 have reported in their study on YouTube videos on dry eye that only a small portion of the videos were of good quality, and that the videos of medical institutes and academic centers were of higher quality than the videos of physicians. Bae and Baxter 12 have evaluated YouTube videos on cataract surgery and found them inadequate in terms of patient training.…”
Section: Discussionmentioning
confidence: 99%
“…Yıldız et al 17 have reported that most YouTube videos on soft contact lenses were of poor quality and reliability, and contained inadequate information. Songur and Citirik 18 have evaluated YouTube videos on retinal detachment surgery and reported the quality of the videos to be poor and the quality of information they provide to be low. Bozali and Yalinbas Yeter 19 argued in their study where they investigated videos on keratoconus that the videos were not adequate as a source of information and did not make a contribution to the patients.…”
Section: Discussionmentioning
confidence: 99%
“…Given that trainee surgeons should acquire knowledge of, and skill in each step of surgery throughout the training process, our study paid attention to individual scoring for each step and presentation of all steps in the videos to achieve educational integrity. It has been emphasized in previous studies that current evaluation systems may not reflect the actual video evaluation results and that current evaluation methods are the result of subjective evaluation ( 20 ). Hence, different results were obtained as a result of each study.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, scores of the Journal of the American Medical Association (JAMA), DISCERN, global quality and usefulness were assessed. DISCERN includes 3 sections and 16 items; each scored (1-5 points) to assess the accuracy of medical information.The DISCERN score (16-75 points) is assessed into 5 groups; from perfect (63-75) to very poor (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). 15 JAMAinvestigates the trustworthiness of online health information with 4 criteria (authorship, attribution, disclosure, and currency).…”
Section: Methodsmentioning
confidence: 99%